SCHOOL EDUCATIONAL MANAGEMENT STRATEGIES IN MANAGING NON-PERMANENT TEACHERS (JOB INSECURITY) AT SDN 02 CIKEMBULAN BANYUMAS - Lilis Widuri; Supriyono; Yeni Lestyarini; Siswadi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze educational human resource management strategies at SDN 02 Cikembulan Banyumas in managing job insecurity among non-permanent teachers as an effort to maintain educational quality. The research employed a qualitative case study approach, with data collected through interviews and observations involving non-permanent teachers at SDN 02 Cikembulan Banyumas. The findings indicate that SDN 02 Cikembulan Banyumas implements several educational managerial strategies, including the provision of a dialogue forum among teachers known as Panggenan Rembug Cikemdu, professional development and training, as well as fair and transparent performance evaluation. These strategies are implemented to maintain teacher quality and professionalism, particularly for non-permanent teachers who experience uncertainty in their professional status. This study concludes that appropriate school educational management strategies, particularly in the context of educational human resource management, are able to maintain teacher professionalism and support the sustainability of educational quality even when teachers are experiencing job insecurity.